2013
DOI: 10.1098/rspb.2013.1468
|View full text |Cite
|
Sign up to set email alerts
|

Finding the ‘lost years’ in green turtles: insights from ocean circulation models and genetic analysis

Abstract: Organismal movement is an essential component of ecological processes and connectivity among ecosystems. However, estimating connectivity and identifying corridors of movement are challenging in oceanic organisms such as young turtles that disperse into the open sea and remain largely unobserved during a period known as 'the lost years'. Using predictions of transport within an ocean circulation model and data from published genetic analysis, we present to our knowledge, the first basin-scale hypothesis of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 33 publications
8
85
1
Order By: Relevance
“…However, recent work has revealed increasingly complex scenarios with other factors, such as swimming behaviour [2,3], mortality [4,5] or intermittent climatic events like storms [6] playing key roles in determining the distributions of marine organisms. In numerous animal species with life cycles characterized by ontogenetic shifts in habitat utilization, population distribution remains insufficiently understood owing to cryptic stages and poorly defined linkages among stages [7]. Deficiencies in basic information on the distribution of such species impede the development of scientifically sound management recommendations and hinder understanding of population biology [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has revealed increasingly complex scenarios with other factors, such as swimming behaviour [2,3], mortality [4,5] or intermittent climatic events like storms [6] playing key roles in determining the distributions of marine organisms. In numerous animal species with life cycles characterized by ontogenetic shifts in habitat utilization, population distribution remains insufficiently understood owing to cryptic stages and poorly defined linkages among stages [7]. Deficiencies in basic information on the distribution of such species impede the development of scientifically sound management recommendations and hinder understanding of population biology [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such techniques are useful for identifying the ecological implications of behavior and generating hypotheses (e.g. Putman et al, 2012;Putman and Naro-Maciel, 2013) that can be further tested with laboratory or field-based experiments (e.g. Mansfield et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the presence of Atlantic individuals within the Mediterranean could prevent the isolation of Mediterranean green nesting populations is an issue that requires further testing with nuclear markers, but several lines of evidence suggest an isolation scenario. The first line of evidence is that no eastern Mediterranean green turtle was detected within our samples or in any Atlantic foraging grounds (MonzonArguello et al, 2010;Proietti et al, 2012), and particle modelling studies indicated that particles originated in the eastern Mediterranean are not able to drift passively into the western basin (Putman and Naro-Maciel, 2013). These results suggest that turtles from the two different origins may not share foraging areas despite both being present within the Mediterranean Sea and Mediterranean green turtles being known to arrive as far as Libya or Tunisia (Godley et al, 2002;Rees et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although no specific studies have been conducted on the putative routes followed by the Atlantic green turtles that feed on the Spanish coasts, previous studies have described the migratory routes for loggerheads (Bolten et al, 1998;Carreras et al, 2006;Monzon-Arguello et al, 2009;Monzon-Arguello et al, 2012) and a general pattern was described for green turtles in the whole Atlantic area (Monzon-Arguello et al, 2010). Furthermore, several studies focused on the modelling of particle drifting, sometimes in addition to genetic studies, have been used to assess movements and distribution either of the Kemp's ridley turtle (Putman et al, 2010; or the green turtle (Putman and Naro-Maciel, 2013), suggesting a strong influence of oceanographic surface currents and indicating the putative routes from each RMU into the vicinity of the different Spanish feeding grounds. Surprisingly, no green turtle from our sample set exhibited any of the haplotypes found in the closest eastern Mediterranean nesting beaches (Encalada et al, 1996;Bagda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%